1999
DOI: 10.1111/j.1574-6968.1999.tb08796.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the syntrophic partners in a coculture coupling anaerobic methanol oxidation to Fe(III) reduction

Abstract: From enrichments with methanol and ferric pyrophosphate a coculture was isolated which coupled methanol oxidation to carbon dioxide with the reduction of Fe(III) to Fe(II). 16S rRNA gene analysis of the isolated syntrophic partners revealed 99.5% similarity to Clostridium sphenoides and 98.5% to Shewanella putrefaciens. Formation of Fe(II) coupled to methanol oxidation was confirmed by using strains of culture collections (C. sphenoides DSM 632 and S. putrefaciens DSM 9461). The importance of this process is d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…Other authors proposed this mechanism as well (e.g. Daniel et al, 1999;Murase and Kimura, 1994b), but, besides circumstantial evidence from rice paddies (Miura et al, 1992), the only supporting data is from marine sediments (Beal et al, 2009 where Fe reduction accounted for 27-72% of anaerobic C mineralization in fens receiving exogenous Fe and 7% with only internally cycled Fe. In a further study in the same peatlands , Fe reduction was a significant process that inhibited methanogenesis.…”
Section: Biogeochemistry and Electron Acceptorsmentioning
confidence: 96%
See 1 more Smart Citation
“…Other authors proposed this mechanism as well (e.g. Daniel et al, 1999;Murase and Kimura, 1994b), but, besides circumstantial evidence from rice paddies (Miura et al, 1992), the only supporting data is from marine sediments (Beal et al, 2009 where Fe reduction accounted for 27-72% of anaerobic C mineralization in fens receiving exogenous Fe and 7% with only internally cycled Fe. In a further study in the same peatlands , Fe reduction was a significant process that inhibited methanogenesis.…”
Section: Biogeochemistry and Electron Acceptorsmentioning
confidence: 96%
“…4; Reaction 2), but the process was not observed in past studies of known Fe(III)-reducers or in AOM studies in peat soils (Smemo and Yavitt, 2007). A study by Daniel et al (1999) found that Fe(III) reduction can be coupled to methanol oxidation by a syntrophic relationship between Shewanella putrefacians and Clostridium sphenoides. They proposed a potentially beneficial reaction ( G • =-782 kJ reaction −1 ) and claimed that this reaction would be slow due to the nature of the syntrophic relationship, but they did not account for the fact that Fe(III) is not available at pH 7.0 in natural waters.…”
Section: Microbiologymentioning
confidence: 96%
“…In the present experiment, iron concentrations ranged between 63 and 83 µg g −1 in the different treatments of the SI soil and between 120 and 140 µg g −1 in the CO soil. The theoretical amount of Fe(III) necessary for the oxidation of 500 µl methane is ca 73 µg g −1 soil (for reaction equation, see Daniel et al, 1999). Thus, enough Fe(III) has been in SI soil to serve as terminal electron acceptor for anaerobic oxidation of methane.…”
Section: Discussionmentioning
confidence: 99%
“…It was also proposed that Fe(III) could serve as electron acceptor for AOM in freshwater wetlands (Murase and Kimura, 1994;Daniel et al, 1999). The reaction is energetically favourable (Smemo and Yavitt, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Methanogens degrade methanol to methane and carbon dioxide (Schnellen, 1947 ;Sowers & Ferry, 1983 ;Ollivier et al, 1984 ;Ni & Boone, 1991). Methanol can also be degraded by syntrophic cultures of anaerobic micro-organisms (Heijthuijsen & Hansen, 1986 ;Cord-Ruwisch & Ollivier, 1986 ;Davidova & Stams, 1996 ;Daniel et al, 1999). However, none of these methanol-degrading micro-organisms is restricted to the use of methanol as a substrate.…”
Section: Of Co #mentioning
confidence: 99%